Pacific Island Countries : In Search of a Trade Strategy - Chen, Hong.; Rauqeuqe, Lanieta; Singh, Shiu raj.; Wu, Yiqun (Washington, D.C. : International Monetary Fund, 2014)
International trade is vital for economic prosperity in Pacific island countries, but their trade performance has been weak over the past decade with the exception of resource-rich countries. Small country size and remoteness from global economic centers may have contributed to this relatively poor performance. However, the emergence of Asia as a global economic center presents Pacific island countries with an unprecedented opportunity to develop trade with Asia, particularly in tourism for a number of PICs. Moreover, if a strong two-way linkage is established between tourism and agriculture, Pacific island countries stands a better chance to improve broad-based growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet